Radiation shielding of the sterilization installation based on gamma-radiating europium isitopes - Razsukovanyj, B.N.; Mazilov, A.A.; Mazilov, A.V. (Вопросы атомной науки и техники, 2004)
The method of calculation of a radiation protection from a source of a gamma radiation including isotopes of
europium-152 and europium-154 by activity 1.5 MCi everyone is presented. As a material of protection the iron,
concrete and homogeneous mixture of iron ore and concrete was used. The way of computation of radiation
parameters necessary for performance of calculation of protection from nontraditional materials is shown. Представлено спосіб розрахунку радіаційного захисту від джерела гамма-випромінювання, що включає в
себе ізотопи європій-152 і європій-154 активністю 1.5 МКи кожний. Як матеріал захисту використано залізо,
бетон і гомогенна суміш залізної руди і бетону. Показано спосіб обчислення радіаційних параметрів,
необхідних для виконання розрахунку захисту з нетрадиційних матеріалів. Представлен способ расчёта радиационной защиты от источника гамма-излучения, включающего в себя
изотопы европий-152 и европий-154 активностью 1.5 МКи каждый. В качестве материала защиты
использованы железо, бетон и гомогенная смесь железной руды и бетона. Показан способ вычисления
радиационных параметров, необходимых для выполнения расчёта защиты из нетрадиционных материалов.